Plant Breeding and Intellectual Property Rights in Nepal - Dilip Raj,; Tiwari, Khusi Ram; Joshi, Bal Krishna; Subedi, Kalidas; Panthee, Pooja (Nepal Public Policy Review, 2023)
This article examines the adoption of plant breeders’ rights (PBR), also known as intellectual property rights (IPR), pertaining to plant breeding and genetics in various nations. Its main goal is to offer direction for the growth of an organized and competitive plant breeding industry in Nepal. The paper seeks to analyze the mechanisms that ensure adequate protection of intellectual property and returns on investment in plant breeding, drawing on international practices and treaties like the Convention on Biodiversity, Trade Related Aspect of Intellectual Property (TRIPS), and the International Union for the Protection of New Varieties of Plants (UPOV). The paper presents case studies to demonstrate how these issues are addressed by looking at the current IPR landscape in Asia, Europe, and North America. These results are the basis of policy recommendations to aid Nepal in developing a strong plant breeding industry.